Do nu na pintura à pintura nua - Moraes, Renato Martins Alves de (2020)
The objective of the present text is the analysis in philosophy and in the visual arts, especially in paintings, of the path taken by the body, through the images of several art works. It was important to state the beginning of the body ́s path through various situations of analysis, critics, and study. The aim regarding the human body was directed specifically at the feminine naked body, vastly represented through the images of divas, nymphs and venus, in addition to the allegories imposed by the Catholic Church. However, this representation was gradually freed from those impositions by the necessary distance required by those allegories, which were helped the artists´ creativity. It was also important to point out the use by those artists of interdicts in philosophy and in the visual arts, to express their artistic needs, representing the feminine naked body, in addition to fallen, transparent and wet draperies revealing its forms and shapes. It was also important to bring the analysis of philosophers and scholars such as Georges Bataille, Daniel Arasse, Giorgio Agamben, Gorges Didi-Huberman, Eliane Robert de Moraes, Kenneth Clark, Gilles Deleuze, David Anfam, among others, regarding artworks of some artists such as Picasso, Manet, De Kooning, Pollock, among others in their respective art movements such as pop art, surrealism, and abstract expressionism, in other to express the point achieved by the paining´s unveiling. In other words, up to the point of the paintings´ own nakedness